Strengthening Youth Awareness on Online Gambling Through Sriwijaya State Polytechhnic and Merlimau Melaka Polytechnic Collaboration - Keti Purnamasari; Kiki Azakia; Rizal Afif Abdullah Napitupulu; Mahmud Junianto; Simmathiri A/L Applainaidu; Nadia Azzahra; Mutiara Syafitri; Naira Sasikirani (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This Community Service program is a collaboration between Politeknik Negeri Sriwijaya and Politeknik Merlimau Melaka, aimed at improving students’ (santri) financial literacy and providing a comprehensive understanding of the risks and negative impacts of online gambling, which has become increasingly prevalent among adolescents. The program began with an initial observation to analyze the needs of the partner institution and to prepare for the implementation of activities. The intervention was carried out at Pondok Pesantren Al-Amalul Khair through several stages, including a pre-test, the delivery of financial literacy material, counseling on the dangers of online gambling, interactive discussions, and a post-test. The pre-test results indicated that the students’ level of financial literacy ranged from low to moderate. After the intervention, there was a significant improvement in their understanding, as reflected in the post-test score of 95,625, rising from the initial score of 65. Overall, this program has generated a tangible impact in enhancing financial literacy, strengthening awareness of online gambling risks, and fostering more responsible financial and digital behavior among the students. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well Being SDG 4: Quality EducationSDG 16: Peace, Justice, and Strong Institutions